2021
DOI: 10.1016/j.chaos.2021.111325
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic probical strategies in a delay virus infection model to combat COVID-19

Abstract: In disease model systems, random noises and time delay factors play key role in interpreting disease dynamics to comprehend deeper insights into the course of dynamics. An endeavor to forecast intercellular behavioral dynamics of SARS-CoV-2 virus via Infection model with responsive host immune mechanisms forms the crux of this research study. Incorporation of time delay factor into infection transmission rates in noisy system epitomizes spectacular view on internal viral dynamics and stability properties are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Many real-world case studies in different countries have showed that the tremendous growth in the healthcare requirements for Covid-19 patients. It is the results of fast person-to-person transmission ( Fidan and Yuksel, 2021 , Pitchaimani and Devi, 2021 ) of the Covid-19 delta variant as well as shortage of suitable strategies for preventing the spreads of virus among groups of confirmed Covid-19 cases to other healthy ones. In addition, the shortage of proper data modelling and short/long-term Covid-19 outbreak forecasting solutions also led to challenges for the governments to effectively manage as well as plan for social resource optimization ( Nascimento et al, 2021 ).The accurate pandemic forecasting mechanism also supports for the governments to properly impose suitable policies to simultaneously deal with the expansion of Covid-19 as well as ensure the social/economic stability ( Miao, Last, & Litvak, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many real-world case studies in different countries have showed that the tremendous growth in the healthcare requirements for Covid-19 patients. It is the results of fast person-to-person transmission ( Fidan and Yuksel, 2021 , Pitchaimani and Devi, 2021 ) of the Covid-19 delta variant as well as shortage of suitable strategies for preventing the spreads of virus among groups of confirmed Covid-19 cases to other healthy ones. In addition, the shortage of proper data modelling and short/long-term Covid-19 outbreak forecasting solutions also led to challenges for the governments to effectively manage as well as plan for social resource optimization ( Nascimento et al, 2021 ).The accurate pandemic forecasting mechanism also supports for the governments to properly impose suitable policies to simultaneously deal with the expansion of Covid-19 as well as ensure the social/economic stability ( Miao, Last, & Litvak, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sarkar et al [ 25 ] predicted the COVID-19 pandemic in India in 2020. Pitchaimani and Brasanna Devi [ 26 ] then used the stochastic delay to model and discuss COVID-19 the following year, in 2021 and also Araz [ 27 ] implemented optimal control on the COVID-19 model in the same year and discussed its impact.…”
Section: Introductionmentioning
confidence: 99%